Psychometric properties of multidimensional life-satisfaction scale on Indonesian college students - Apriliana, I Putu agus; Suranata, Kadek (Institute of Advanced Engineering and Science, 2025)
College students face various challenges, making the emphasis on life satisfaction increasingly important. To promote life satisfaction in higher education specifically in Indonesia, highlighting a valid and reliable measurement tool is necessary. The multidimensional life-satisfaction scale (MLSS) has been widely used, but its psychometric properties require evaluation for application among college students in Indonesia. Hence, this study investigates the psychometric properties of the MLSS, involving 651 Indonesian college students who completed an online survey. Data were collected using the original 40-item Indonesian version of the MLSS and factor analysis was conducted to assess construct, convergent, and discriminant validity. Internal consistency was evaluated using Cronbach’s alpha. Exploratory factor analysis (EFA) establishes a five-factor solution and confirmatory factor analysis (CFA) confirms the second model with fourteen items met the goodness-of-fit. The five constructs (family, friends, campus, environment, and self) indicate well enough score both on average variance extracted (AVE) (range from .50 to .64) and composite reliability (range from .66 to 80). Internal consistency was acceptable, and correlations between constructs were significant. All items demonstrated sufficient factor loading. The short-form self-report model of the MLSS was found to be valid and reliable for use with college students in Indonesia.